Aldosterone Response in Severe Hypokalemia and Volume Depletion: A Case Report and Review of the Recent Research. (20th July 2016) - Kai, Keiko; Tominaga, Naoto; Uchida, Daisuke; Fukai, Nanae; Matsuura, Yumie; Uda, Susumu; Yokochi, Akio
Abstract : We report a case of severe hypokalemia and volume depletion complicated by chronic watery diarrhea resulting from chronic alcoholism in a 57-year-old man. Prompt replacement of normal saline with potassium chloride and cessation of alcohol intake resulted in a favorable outcome. We discuss the pathophysiology of the case, emphasizing the response of aldosterone in both hypokalemia and volume depletion, and provide a review of recent research.